2017
DOI: 10.1166/asl.2017.9229
|View full text |Cite
|
Sign up to set email alerts
|

Frame Effects on Outdoor–Indoor Transmission Class of Fixed and Open Glass Windows

Abstract: The effect of a frame around glass fixed windows on outdoor-indoor transmission class (OITC) was studied here. Three frame materials were selected, i.e. timber, Aluminum and unplasticized Poly Vinyl Chloride (uPVC). The use of real open window (to differentiate it from partially open double layered window) for natural ventilation was also studied. The top hung style was selected due to common usage and the possibility of noise blockage by the shutter. Laboratory test complies with ASTM E-90 was employed. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The sound insulation performance of the NRVW opening is better than that of an opened woodframed glass window. Mediastika, Kristanto, Anggono, Suhedi, & Purwaningsih, 2017 showed that even a small opening at a glass (5 mm thick) window created for ventilation could drop the sound insulation performance of the window from OITC 24 to OITC 7 ( Figure 10). Hence, based on these experimental results, the NRVW opening can be combined with a fixed glass window to fulfil the fresh air need and reduce noise entering the room instead of opening the window and letting the fresh air and noise in.…”
Section: Acoustical Simulationmentioning
confidence: 99%
“…The sound insulation performance of the NRVW opening is better than that of an opened woodframed glass window. Mediastika, Kristanto, Anggono, Suhedi, & Purwaningsih, 2017 showed that even a small opening at a glass (5 mm thick) window created for ventilation could drop the sound insulation performance of the window from OITC 24 to OITC 7 ( Figure 10). Hence, based on these experimental results, the NRVW opening can be combined with a fixed glass window to fulfil the fresh air need and reduce noise entering the room instead of opening the window and letting the fresh air and noise in.…”
Section: Acoustical Simulationmentioning
confidence: 99%